Using storytelling to promote organizational resilience: An experimental study of different forms of risk communication - Andrea Kampmann; Burkhard Pedell (Schmalenbach Journal of Business Research (SBUR), 2022)
In this experimental study, we compare the influence of risk communication in the form of stories versus statistics on the level of investment in a resilience-promoting activity. We also analyze how this influence interacts with time gap and with an individual's preferences for risk and numbers. The results indicate that individuals invest more in a resilience-promoting activity when communication comes as a story. This finding holds irrespective of an individual's risk preference. The results did not confirm the expectation that communication in story form leads to a more enduring effect than communication in statistical form. The expectation that the preference for numbers influences the effectiveness of a specific communication form was also not confirmed.
Keywords: D81; D83; G32; 650; Storytelling; Risk Communication; Organizational Resilience; Risk Management; Experiment